Local Economic Development and Regional Autonomy: The Role of Local Government in Implementing the Coastal Community Development Movement Program (Gerbang Mapan) in The Coastal Areas of Tangerang Regency - Farid, Abdul Rohman; Stiawati, Titi; Sobirin, Haris; Rinky, Maicy Vidini; Bachtiar, Tubagus Achmad; Heningtias, Nimas Diah (Future Science, 2026)
Indonesia, as an archipelagic country, holds substantial coastal economic potential, yet this potential is often accompanied by disparities and the resource paradox that limit community welfare. This study examines conditions in the coastal areas of Tangerang Regency, which are characterized by low fisheries productivity, limited access to technology, markets, and infrastructure, as well as environmental issues such as mangrove degradation and coastal abrasion. The research aims to analyze the role of local government and evaluate the implementation of the Gerbang Mapan Program. This study applies a descriptive qualitative approach with policy analysis, using data from Statistics Indonesia (BPS), the Ministry of Marine Affairs and Fisheries (KKP), regional spatial planning documents (RTRW), and relevant literature. The findings show a significant gap between existing potential and actual conditions, with economic activities still dominated by low-productivity traditional enterprises. The implementation of the Gerbang Mapan Program indicates limited progress when assessed through George Edward III’s framework, particularly in terms of communication, resources, disposition, and bureaucratic structure. Despite these limitations, the program has produced several positive impacts, including increased community income, the development of small enterprises, mangrove rehabilitation, and greater community participation. In conclusion, strengthening integrated, adaptive, and sustainable policy governance is essential to bridge existing gaps. Efforts should focus on improving market access, enhancing institutional capacity, and increasing human resource competencies to support inclusive and sustainable coastal economic development.